Lipopolysaccharide Alters the m6A Epitranscriptomic Tagging of RNAs in Cardiac Tissue - Han, Ye-Chen; Xie, Hong-Zhi; Lu, Bo; Xiang, Ruo-Lan; Zhang, Hai-Peng; Li, Jing-Yi; Zhang, Shu-Yang (Frontiers in Molecular Biosciences, 2021)
N6-methyladenosine (m6A) modification plays important roles in the pathology of a variety of diseases. However, the roles of m6A modification in sepsis-induced myocardial dysfunction are not well defined. Rats were divided into control and lipopolysaccharide (LPS)-induced sepsis group. Global m6A levels of left ventricle tissue were measured by LC-MS/MS, and transcriptome-wide m6A modifications were profiled using epitranscriptomic microarrays (mRNAs and lncRNAs). Bioinformatics analysis was conducted to understand the functional implications of m6A modifications during sepsis. Methylated lncRNAs and mRNAs were measured by m6A single-base site qPCR. The global m6A levels in left ventricle tissue were significantly decreased in the LPS group. While 27 transcripts (23 mRNAs and four lncRNAs) were hypermethylated, 46 transcripts (39 mRNAs and 7 lncRNAs) were hypomethylated in the LPS group. The mRNA expression of writers and readers was significantly decreased in the LPS group. The m6A modification of Clec1b, Stk38l and Tnfrsf26 was associated with platelet activation and apoptotic pathways. Moreover, the decrease in m6A modification of lncRNA XR_346,771 may be related to cation import in cardiac tissue. Our data provide novel information regarding changes to m6A modifications in cardiac tissue during sepsis, and m6A modifications might be promising therapeutic targets.